Authority of the Village Head in Appointing and Removing Village Equipment Based on Regulation of the Minister of Internal Affairs Number 67 of 2017 - Junaidi Junaidi; Mila Surahmi; Citra Dewi Saputra (CV. Rayyan Dwi Bharata, 2023)
The administration of village government has an organizational structure for village governance led by a head who is appointed based on community agreement with an election mechanism regulated in laws and regulations, namely Law Number 6 of 2014 concerning Villages, the village head in running the wheels of government is assisted by a secretary village officials and village government officials, the existence of village officials is often a polemic against the process of appointing and dismissing village officials considering the limited number of village officials, while many local people want village officials as a form of community service, so problems arise with the interpretation of who has the authority to appoint and dismissed village officials.